Pseudomonas pseudomallei resistance to beta-lactam antibiotics due to alterations in the chromosomally encoded beta-lactamase. - Godfrey, A J (1991)
Pseudomonas pseudomallei, the causative agent of melioidosis, is generally susceptible to some of the newer extended-spectrum cephalosporins or to combinations of a beta-lactam and clavulanic acid, a beta-lactamase inhibitor. Resistance to these agents may, however, emerge during treatment. We report on alterations in the chromosomal beta-lactamase associated with the development of resistance. Three resistance patterns resulted from three different mechanisms in the strains investigated. Derepression of the chromosomal enzyme resulted in a general increase in the MICs of all of the beta-lactams tested. The second mechanism observed was an insensitivity to inhibition of the beta-lactamase by clavulanic acid. In this case, the level of susceptibility to beta-lactams as independent entities remained unchanged. The final "resistance" pattern occurred in a patient treated with ceftazidime and resulted in a beta-lactamase that was capable of hydrolyzing this antibiotic at detectable levels, but with reduced efficacy against other beta-lactams. The net result was a strain that was generally susceptible to all of the beta-lactams tested except ceftazidime. In all cases, the level of susceptibility to antibiotics other than beta-lactams remained unchanged. Such variability found within one genus over a relatively short time course suggests that treatment of infections caused by this organism should be carefully monitored to detect susceptibility alterations to the chosen therapy.